ON CERTAIN TOPOLOGICAL STRUCTURES OF 2- NORMED SPACE VALUED ORLICZ SPACE  c0 ((S, ||.,.||), Φ, u– ) OF NULL SEQUENCES - Pahari, Narayan Prasad (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The aim of this paper is to introduce and study a new class c0 (( S, ||. , .||), F , ) of 2-normed space valued vector sequences using Orlicz function as a generalization of the basic space c0 of all converging sequences. Beside the investigation pertaining to the linear space structures of the class c0 (( S, ||. , .||), F , ) with some topological properties, our primarily interest is to explore the containment relation of the class c0 (( S, ||. , .||), F , ) in terms of different values of . Keywords: Sequence space, Normal Space , 2- normed Space, Orlicz Function, Orlicz Space. 2010 AMS Subject Classification: Primary - 46A45, Secondary - 46B 15